A New Type of Coincidence and Common Fixed Point Theorem with Applications. (30th April 2014) - Singh, Shyam Lal; Kamal, Raj; De la Sen, Manuel; Chugh, Renu
Abstract : Coincidence and common fixed point theorems for a class of Ćirić-Suzuki hybrid contractions involving a multivalued and two single-valued maps in a metric space are obtained. Some applications including the existence of a common solution for certain class of functional equations arising in a dynamic programming are also discussed.